Case managers in oncology. A literature review (European journal of volunteering and community-based projects, 2023)
Objective: Modern healthcare systems are constantly looking for new organizational models to answer patients' needs. In the oncology field, the organizational model based on Disease Units is becoming established. These systems see the patient at the center and are based on multidisciplinary collaboration between healthcare professionals. In the context of the Disease Units, there should be a professional figure in the nursing field called a case manager, with the role of supporting coordination between the various professionals in charge and guiding the patient in the treatment process. The objective of the work is to understand in depth the context, characteristics, advantages, and barriers to the establishment of this figure.Methodology: The article uses a structured review of international literature.Results: The analysis of 19 articles denotes the need for the case manager to acquire both technical but above all, non-technical skills, such as kindness, humor, and empathy. Results highlight the strategic role of this figure in supporting the patient, especially in improving the quality of life, in adherence to treatment and in the management of the psychological and social sphere, thus strengthening the concept of a healthcare system that sees the patient in the center. Although there are obstacles to the formal establishment of this figure, regulatory changes should be carried out in the coming years to encourage the introduction of case managers within the Disease Units.Originality: The article aims to analyze the characteristics of this professional figure in oncology, whose role is presumed to become increasingly strategic over time.